To Be More Accurate: A Study to Investigate the Importance of Explicit Teaching in Monolingual Language Classroom Settings - Aral, Buse; Dogan, Seval; Oliver, B. Warren (Elsevier Science Bv, 2016)
The purpose of this experimental action research was to examine the effectiveness of explicit teaching in reducing the number of the mistakes made by Turkish foreign language learners at lower levels who have difficulty with the accurate use of to be in sentence structure. It was conducted by a team of 2 teachers on 40 students in two different classes at a private university in Istanbul, Turkey. Data was collected via the gross number of mistakes made on prompts given before and after the treatment and analyzed with the help of SPSS and G-Power software. While found to be statistically insignificant because of a small sample size, the results of this study found that both implicit and explicit teaching methods were effective in teaching students. At the same time, the results implied that implicit education is more advantageous to the student. In this way, this particular project should serve as a base for more statistically sound future research to explore the importance given to the usage of L1 and explicit teaching in monolingual language classroom settings. (C) 2016 The Authors. Published Elsevier Ltd.
International Conference on Teaching and Learning English as an Additional Language (GlobELT) -- APR 14-17, 2016 -- Antalya, TURKEY
Keywords: Implicit Teaching; Explicit Teaching; Use Of L1; Lnaguage Accuracy; State Verb Be; Monolingual Classrooms; Grammar